The Influence of Financial Derivatives, Financial Leases and Institutional Ownership on Tax Avoidance - Wicaksana, Wafi; Putra, Yananto Mihadi (Economics & Islamic Finance Journal (ECIF), 2024)
This research falls under the category of quantitative research, aiming to ascertain the impact of the variables Financial Derivatives, Financial Leases, and Institutional Ownership on the variable Tax Avoidance. The study focuses on manufacturing companies listed on the Indonesia Stock Exchange, employing a purposive sampling method that yields a sample size of 19 companies. The analysis is conducted with a 5% significance level, utilizing the Panel Data Regression Analysis Method facilitated by the E-Views 12 computer program. The findings of the analysis reveal that (1) there is no statistically significant effect of financial derivatives on tax avoidance, (2) there is a significant effect of financial leases on tax avoidance, and (3) there is no significant effect of institutional ownership on tax avoidance.